Act like a leader, think like a leader - Ibarra, Herminia, 1961- (Boston, Massachusetts : Harvard Business Review Press, 2023)
"You aspire to lead with greater impact. The problem is, you're busy executing on today's demands. You know you have to carve out time from your "day job" to build your leadership skills, but it's easy to let immediate problems and old mindsets get in the way. Herminia Ibarra-renowned leadership expert at London Business School-shows how individuals at all levels can step up to leadership by making small but crucial changes in their jobs, their networks, and themselves. In Act Like a Leader, Think Like a Leader, Ibarra offers advice to: Redefine your job in order to make more-strategic contributions; diversify your network so that you connect to, and learn from, a wider range of stakeholders; and become more playful with your self-concept, allowing your familiar (and possibly outdated) leadership style to evolve. Ibarra turns the usual leadership advice-to generate insight about yourself through reflection and analysis of your strengths and weaknesses-on its head by arguing that you must first act and experiment your way into trying new things. The valuable external perspective you gain from direct experiences and experimentation, which Ibarra calls "outsight," provides new and critical information on what kind of work is important to you, how you should invest your time, why and which relationships matter, and, ultimately, who you want to become. Packed with self-assessments and practical advice that you can implement immediately, this book gives you the tools to start acting like a leader and to advance your career to the next level"--
The "Outsight" Principle: How to Act and Think Like a Leader -- Redefine Your Job -- Network Across and Out -- Be More Playful with Your Self -- Manage the Stepping-Up Process -- Act Now.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 26, 2023).
OCLC control number change
Keywords: Leadership; Executive ability; Organizational change; Motivation (Psychology); Executive ability; Leadership; Motivation (Psychology); Organizational change; elektronické knihy; electronic books